The Adaptive Nature of the Bone-Periodontal Ligament-Cementum Complex in a Ligature-Induced Periodontitis Rat Model. (26th June 2013) - Lee, Ji-Hyun; Lin, Jeremy D.; Fong, Justine I.; Ryder, Mark I.; Ho, Sunita P.
Abstract : The novel aspect of this study involves illustrating significant adaptation of a functionally loaded bone-PDL-cementum complex in a ligature-induced periodontitis rat model. Following 4, 8, and 15 days of ligation, proinflammatory cytokines (TNF- α and RANKL), a mineral resorption indicator (TRAP), and a cell migration and adhesion molecule for tissue regeneration (fibronectin) within the complex were localized and correlated with changes in PDL-space (functional space). At 4 days of ligation, the functional space of the distal complex was widened compared to controls and was positively correlated with an increased expression of TNF- α . At 8 and 15 days, the number of RANKL(+) cells decreased near the mesial alveolar bone crest (ABC) but increased at the distal ABC. TRAP(+) cells on both sides of the complex significantly increased at 8 days. A gradual change in fibronectin expression from the distal PDL-secondary cementum interfaces through precementum layers was observed when compared to increased and abrupt changes at the mesial PDL-cementum and PDL-bone interfaces in ligated and control groups. Based on our results, we hypothesize that compromised strain fields can be created in a diseased periodontium, which in response to prolonged function can significantly alter the original bone and apical cementum formations.